Skills shortage and innovation openness - Paolo Carioli; Dirk Czarnitzki (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Skills shortage has become a key policy issue in highly developed and innovation-oriented economies, with non-negligible consequences on firms' innovation activities. We investigate the effect of skills shortage on firms' innovation openness, which is considered to be one of the key drivers of innovation performance. We hypothesize that scarcity of personnel causes firms to cooperate more broadly with external partners. Using cross-sectional data from the German contribution to the Community Innovation Survey (CIS), and exploiting detailed information on the extent to which firms could fill their job vacancies, we find that, on average, a one standard deviation increase in skills shortage more than doubles a firm's cooperation breadth. We contribute to the literature on human capital in relation to open innovation by characterizing the necessity of openness as a way to mitigate the scarcity of skills.
Keywords: O36; J63; 330; open innovation; R&D collaboration; skills shortage